10 Simple Rules for Integrating Ethics Training into Any Quantitative Course. Issue 1 (2nd January 2023) - Tractenberg, Rochelle
Abstract: This article presents two principal "rules" that instructors should use professional ethical practice standards, not issues, to guide instruction/learning objectives, and use instructional and/or curriculum development guidelines to ensure that changes to courses are systematic and yield actionable student outputs. It presents resources to serve learners because they offer tools and techniques that equip future practitioners to practice ethically - whenever they practice. The article describes how learning outcomes of integrated ethics within a mathematics, statistics, or data science course featuring the ASA Ethical Guidelines and the ACM Code of Ethics, will result in individuals trained in how to practice ethically, rather than individuals who completed a required ethics course or mastered "ethics content".